Radionuclide contamination in agricultural and urban ecosystems: A study of soil, plant, and milk samples - Aichouche Mohamed E.A.; Petrović Mihajlo V.; Živković Milena P.; Krstić Dragana Ž.; Branković Snežana R. (Kragujevac Journal of Science)
This study investigates the presence of radionuclides in soil, plant, and milk samples from rural and urban areas. Using gamma spectrometry, the activity concentrations of radionuclides were measured to assess potential exposure pathways for external gamma radiation and radionuclide transfer through the food chain. Higher activity levels were generally observed in rural environments, while certain plant and milk samples revealed trace contamination. These findings underscore the importance of continuous environmental monitoring to safeguard food safety and mitigate risks associated with radiological contamination.